Assessing implant position and bone properties after cementless total knee arthroplasty using weight-bearing computed tomography - Lin, Jane; Zamani, Mariam; Kalia, Vishal; Vasarhelyi, Edward M.; Lanting, Brent A.; Teeter, Matthew G. (BMC musculoskeletal disorders, 2025)
Background Weight-bearing CT (WBCT) scanners are growing in availability and provide the capability of three-dimensional imaging while a joint is under load. This may be particularly useful in relation to personalized total knee arthroplasty (TKA) with cementless implants. The objective of the present study was to evaluate the utility and inter-observer repeatability of WBCT in assessing patients with cementless TKA in a loaded position. Methods Forty patients who underwent primary TKA approximately 3 years previously and received one of two cementless implant systems were recruited, including two subjects with bilateral TKA, for a total of 42 knees. All subjects underwent examination of their knee with WBCT while standing, thereby loading the indicated knee. Lateral distal femoral angle (LDFA), medial proximal tibial angle (MPTA), hip-knee-ankle angle (HKAA), and joint line obliquity (JLO) were measured on full length radiographs and the WBCT exams by two observers. Femoral and tibial component rotation was measured on WBCT. Greyscale values representing bone density were assessed in five identically sized regions of interests in both the femur and the tibia on WBCT. Results Inter-observer agreement for alignment was good (95% ICC: 0.87). Inter-observer agreement for femoral component rotation was moderate (95% ICC: 0.67) and for tibial component rotation was good (95% ICC: 0.84). Inter-observer agreement for femoral greyscale values was good (95% ICC: 0.87) and for tibial greyscale values was excellent (95% ICC: 0.97). Conclusion Cementless TKA can be assessed postoperatively using WBCT to measure implant position and bone density in a functional, loaded joint position with good inter-observer repeatability.